Crown‐ether‐mediated crystal structures of the glycosyltransferase PaGT3 from Phytolacca americana. Issue 6 (4th June 2020) - Maharjan, Rakesh; Fukuda, Yohta; Nakayama, Taisuke; Nakayama, Toru; Hamada, Hiroki; Ozaki, Shin-ichi; Inoue, Tsuyoshi
Abstract : Crystal structures of the glycosyltransferase Pa GT3 crystallized in the presence of crown ethers provide a basis for understanding its acceptor‐recognition mechanism. Abstract : Uridine diphosphate glycosyltransferases (UGTs) are ubiquitous enzymes that are involved in the glycosylation of small molecules. As glycosylation improves the water solubility and stability of hydrophobic compounds, interest in the use of UGTs for the synthesis of glycosides of poorly soluble compounds is increasing. While sugar‐donor recognition in UGTs is conserved with the presence of a plant secondary product glycosyltransferase (PSPG) motif, the basis of the recognition of the sugar acceptor and the regioselectivity of the products is poorly understood owing to low sequence identity around the acceptor‐binding region. Pa GT3, a glycosyltransferase from the plant Phytolacca americana, can glycosylate a range of acceptors. To illustrate the structure–function relationship of Pa GT3, its crystal structure was determined. The sugar‐donor and sugar‐acceptor binding pockets in Pa GT3 were recognized by comparison of its structure with those of other UGTs. The key feature of Pa GT3 was the presence of longer loop regions around the hydrophobic acceptor‐binding pocket, which resulted in a flexible and wider acceptor binding pocket. In this study, Pa GT3 crystals were grown by co‐crystallization with 18‐crown‐6 ether or 15‐crown‐5 ether. The crown‐ether molecule in the asymmetric unit was observed to form a complex with a metal ion, which was coordinated on two sides by the main‐chain O atoms of Glu238 from two molecules of the protein. The crown ether–metal complex resembles a molecular glue that sticks two molecules of Pa GT3 together to enhance crystal growth. Thus, this result provides an insight into the substrate‐recognition strategy in Pa GT3 for the study of glycosyltransferases. Additionally, it is shown that crown ether–metal ion complexes can be used as a molecular glue for the crystallization of proteins.